2018
DOI: 10.1038/s41598-018-27513-y
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition on the stop signal task improves during cardiac contraction

Abstract: Motor actions can be facilitated or hindered by psychophysiological states of readiness, to guide rapid adaptive action. Cardiovascular arousal is communicated by cardiac signals conveying the timing and strength of individual heartbeats. Here, we tested how these interoceptive signals facilitate control of motor impulsivity. Participants performed a stop signal task, in which stop cues were delivered at different time points within the cardiac cycle: at systole when the heart contracts (T-wave peak, approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 41 publications
6
62
0
Order By: Relevance
“…Moreover, activation of the right anterior insula and middle frontal cortex during stop as compared to go trials of the stop signal task, an index of prepotent response inhibition, negatively correlates with motor and nonplanning impulsivity scores (Farr, Hu, Zhang, & Li, 2012). Furthermore, response inhibition on the stop signal task is improved during momentary states of cardiovascular arousal when the heart contracts (Rae et al, 2018), suggesting a critical role of insula function in impulsivity. Noteworthy, apart from insular cortex, other areas such as somatosensory cortex or inferior frontal gyrus have been implicated in interoceptive abilities (e.g., Adolfi et al, 2017;Pollatos, Schandry, Auer, & Kaufmann, 2007) as well as impulsive behaviors (e.g., Deng et al, 2017;Rae, Hughes, Weaver, Anderson, & Rowe, 2014;Zhang et al, 2015), suggesting further areas of functional overlap between impulsivity and interoception.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, activation of the right anterior insula and middle frontal cortex during stop as compared to go trials of the stop signal task, an index of prepotent response inhibition, negatively correlates with motor and nonplanning impulsivity scores (Farr, Hu, Zhang, & Li, 2012). Furthermore, response inhibition on the stop signal task is improved during momentary states of cardiovascular arousal when the heart contracts (Rae et al, 2018), suggesting a critical role of insula function in impulsivity. Noteworthy, apart from insular cortex, other areas such as somatosensory cortex or inferior frontal gyrus have been implicated in interoceptive abilities (e.g., Adolfi et al, 2017;Pollatos, Schandry, Auer, & Kaufmann, 2007) as well as impulsive behaviors (e.g., Deng et al, 2017;Rae, Hughes, Weaver, Anderson, & Rowe, 2014;Zhang et al, 2015), suggesting further areas of functional overlap between impulsivity and interoception.…”
Section: Discussionmentioning
confidence: 97%
“…In the domain of reactive response inhibition, we previously found that stopping efficiency, as measured by stop signal reaction times on the stop signal task, was enhanced if the stop cues were presented at cardiac systole (Rae et al, 2018). Here, we extend this observation from reactive motor inhibition to examine the volitional withholding of actions, i.e.…”
Section: Cardiac Cues To Inhibitory Processesmentioning
confidence: 63%
“…Physiological signals from the body influence emotion, cognition, and action (Damasio, 1996;Garfinkel & Critchley, 2016;Tsakiris & Critchley, 2016). This includes heartbeats, which can cue more efficient response inhibition (Rae et al, 2018). We tested whether these effects extend to intentional inhibition, in which participants choose whether to act, or to withhold movements, with Choose cues presented at either cardiac systole or diastole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations